In Memory of Rosemary Ganzert Fischer - Colin Andrew Lee (Voices)
Dr. Rosemary Ganzert Fischer (1932-2021) was a pioneer of Canadian music therapy. She began the Bachelor of Music Therapy programme at Wilfrid Laurier University (WLU), Waterloo, Ontario in 1986. This article describes her contributions to Canadian music therapy. It also contains memories of our time working and teaching together and the inspirations we shared. Rosemary’s legacy to Canadian music therapy should be remembered. The dedication she brought to her work and teachings at WLU inspired a generation of music therapists who are now actively working and standing on the shoulders of her contributions to the field.